LINGUO-STYLISTIC ANALYSIS OF ENGLISH TRANSLATIONS OF ONE POEM BY GALAKTION TABIDZE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article deals with the linguo-stylistic analysis of English translations of the poem “Snow” by Galaktion Tabidze. The translations are made by three different translators. It was important for us to find out if the translators were able to understand Galaktioni's poetry and translate it into English, maintaining the musicality of the poem, the euphony of the sounds and the tropes that stand out with great originality in the poem we have mentioned. The research revealed that the translations of the poem by two foreign translators lack artistry and are a bit dry, that is because at the time of translating the poem, they still did not know the Georgian language thoroughly. Translation made by famous Georgian translator Innes Merabishvili has to be recognized as an irreplaceable example of artistic translation.